Development of a continuous cardiac output sensor - Ho, Eddy Yoong Ching. (2008)
A continuous cardiac output monitoring system was developed in the laboratory to allow in vivo cardiac output measurements. It comprises a blood velocity sensing module and a blood vessel cross-sectional area measurement module. The velocity sensing probe consists of two optical fibres sleeved in a catheter. The laser beam is coupled into one of the fibres and projected into the blood through the side of the probe. The back-scattered light from the erythrocytes within the probe volume is collected by the other fibre. This optical signal is processed for the Doppler frequency shift information via the signal processing unit and a spectrum analyser.